Aktivitas Antioksidan Ekstrak Etanol Buah, Daun, Batang Dan Rimpang Pada Tanaman Wualae (Etlingera Elatior (Jack) R.M Smith) (RECTRACTED): Antioxidant Activity of Ethanol Extract of Fruits, Leaves, Stems and Rhizome of Wualae (Etlingera elatior (Jack) R.M Smith) (RECTRACTED) - Jabbar, Asriullah; Wahyuni, Wahyuni; Malaka, Muh Hajrul; Apriliani, Apriliani (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2019)
This paper is retracted by editor because it has been published in another journal Wualae (Etlingera elatior (Jack) R.M Smith) is one of the plants in the Zingiberaceae family, widely used in medicine ranging from rhizomes, fruits, and flowers. Empirically Wualae are usually used by people for treating skin diseases, flavoring food, a natural soap, and in Southeast Sulawesi, it is used to treat typhoid fever. This study aims to examine the antioxidant activity of Wualae (Etlingera elatior) plant. The plant extracts were extracted by maceration method, antioxidant activity test was performed by 2,2-Diphenyl-1-picrylhydrazyl (DPPH) method. The results showed that ethanol extracts of fruits, leaves, stems and rhizomes of Wualae (Etlingera elatior) has the potential antioxidant activity with the IC50 values of 72.518 mg/L, 99.890 mg/L, 52.345 mg/L and 58.638 mg/L, respectively. and Vitamin C has IC50 value of 3,787 mg/L.